Treinamento proprioceptivo em pacientes com artrite reumatoide: revisão sistemática - Silva, Kelson Nonato Gomes da [UNIFESP] (2010)
Objective: To assess the effectiveness and safety of balance training (proprioceptive training) to improve functional capacity in patients with rheumatoid arthritis. Methods: Systematic review with Cochrane methodology. Search strategy: Databases Cochrane Central Register of Controlled Trials (The Cochrane Library 2008, Issue 4), MEDLINE (1966 to 2008) via PubMed, EMBASE (1980 to 2008), LILACS (1982 to 2008), CINAHL (1982 to 2008), PEDro e Scirus. We also carried out a handsearching and contact professional associates of the eligible studies when necessary. There was no language restriction. Selection criteria: All eligible randomised controlled trials or controlled clinical trials comparing balance training (proprioceptive training) with any other intervention or with no intervention, in patients with rheumatoid arthritis of according to the 1987 American College of Rheumatology (ACR) criteria. Data collection e analysis: Two reviewers independently assessed titles and/or abstracts for inclusion criteria and for risk of bias. Results: The electronic search identified 864 studies. From this search, 17 studies described general exercises in rheumatoid arthritis patients as the main topic. After analysing them, we observed that the main outcomes were improvement in muscle strength, endurance, and dynamic exercises (swimming, walking, etc). As we did not find any studies investigating the effects of proprioceptive training alone in patients with rheumatoid arthritis, it was not possible to include any data regarding the chosen topic in our systematic review. Conclusion: There is no research available examining the efficacy of balance training in patients with rheumatoid arthritis. The effectiveness and safety of balance training to improve functional capacity of these patients remains unclear, however, it is suggested that future research should give more importance to the balance training by either increasing the number and duration of sessions or investigating its efficacy alone.